Nickel-catalyzed aminocarbonylation of aryl halides using carbamoylsilane as an amide source. Issue 71 (21st September 2017) - Wen, Xue-Ping; Han, Yu-Ling; Chen, Jian-Xin
Abstract : The nickel-catalyzed aminocarbonylation reaction of aryl halides using carbamoylsilanes as an amide source in toluene is developed leading to the formation of some tertiary or secondary aryl amides in good yields. Abstract : The nickel-catalyzed aminocarbonylation of aryl halides using carbamoylsilane as an amide source is developed. The procedure can prepare both tertiary and secondary amides, and is applicable to various carbamoylsilanes and aryl halides containing different functional groups. The types and the relative position of substituents on the aryl ring impact the coupling efficiency.